REVITALIZING REVISIT INTENTIONS: Unravelling the nexus of emotional solidarity and leisure event experiences in Ghana - Asimah Kweku Vincent, - (2023)
ABSTRACT REVITALIZING REVISIT INTENTIONS: UNRAVELLING THE NEXUS OF EMOTIONAL SOLIDARITY AND LEISURE EVENT EXPERIENCES IN GHANA By Vincent Kweku Asimah NIM 2010388 (vkasimah@upi.edu) Under the Guidance of Prof. Dr. Ratih Hurriyati, M.P. Prof DR Vanessa Gaffar, SE Ak, MBA Dr. Lili Adi Wibowo, S.Pd., S.Sos., M.M The study examines the role of emotional solidarity in enhancing intrinsic motivation, satisfaction, and loyalty among leisure event visitors in Ghana. The study aims to explore the influence of emotional solidarity, segment visitors based on their emotional solidarity levels, and examine the relationship between different visitor motivations and their behavioural and revisit intentions. The research also outlines the plans and contributions of the Ghana Tourism Authority to the development of leisure events in Ghana and design a framework that matches the combined effect of visitor emotional solidarity, motivation, and leisure attachment. A mixed-method approach is employed, combining both quantitative and qualitative data, with 461 event visitors/tourists and 3 top management members of Ghana Tourism Authority participating in the study. This study examines the relationships between emotional solidarity, intrinsic motivation, behaviour, and revisit intentions within the context of leisure events. The findings demonstrate that emotional solidarity positively influences intrinsic motivation, which in turn drives behaviour during leisure event experiences. Additionally, the study reveals a strong link between behaviour and individuals' intentions to revisit the destination. The research also highlights the significant contributions of the Ghana Tourism Authority (GTA) in enhancing the development of leisure events in Ghana through strategic partnerships, targeted marketing campaigns, and investment in event infrastructure. The study underscores the importance of tailoring marketing efforts and establishing emotional connections with visitors based on their varying levels of emotional solidarity and motivations. These findings have practical implications for policymakers, practitioners, and the GTA, providing insights for effectively promoting and improving leisure event experiences in Ghana. Keywords: Emotional Solidarity; Leisure events, Cultural festival; Motivation; Ghana.